Developing Customer Loyalty : A Case Study of National Bank of Oman - Rao, D.N.; Shankaraiah, K.; Al Hakmani, Ali (Indian Journal of Marketing, 2004)
Today, the growth of E-banking is revolutionizing the banking industry globally. The banks are gradually displacing the traditional method (face-to-face) of doing business with more of technology driven self-services to satisfy demanding customers. The traditional methods of retail banking focused more on convenience, and service quality and emphasized the same in their marketing communications to develop customer loyalty. With the emergence of E-banking phenomena, the nature and scope of retail banking service provision has undergone drastic changes. A number of banks are working to develop Internet as a service delivery medium and co-ordinate customer relationship management in the context of multiple media, including websites, call-centers, kiosks, ATMs and branches.